130k views
2 votes
Simplify the expression 5+6i/4+6i

A) 56-6i/-20
B) -16-6i/-20
C)56-6i/52
D) -16-6i/52

1 Answer

6 votes

Answer:


The\ simplified\ form\ of\ the\ (5 + 6i)/(4 + 6i)\ is\ (56-6i)/(52).

Option (C) is correct .

Explanation:

As the expression given in the question as follows.


= (5 + 6i)/(4 + 6i)

Now rationalize the expression.


= (5 + 6i* 4 - 6i)/(4 + 6i* 4 - 6i)

Using the formula

a² - b² = (a - b) (a + b)

Using in the above


= (5 + 6i* 4 - 6i)/((4)^(2) - (6i)^(2))


= (5* 4-5* 6i+6i* 4-36\ i^(2))/(16 - 36(i)^(2))

As i² = -1


= (20-30i+24i+36)/(16 + 36)


= (56-6i)/(52)


Therefore\ the\ simplified\ form\ of\ the\ (5 + 6i)/(4 + 6i)\ is\ (56-6i)/(52).

Option (C) is correct .

User Satyaki Sanyal
by
5.9k points